2009
DOI: 10.1016/j.mimet.2009.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex real-time PCR for detection, identification and quantification of ‘Candidatus Liberibacter solanacearum’ in potato plants with zebra chip

Abstract: The new Liberibacter species, 'Candidatus Liberibacter solanacearum' (Lso) recently associated with potato/tomato psyllid-transmitted diseases in tomato and capsicum in New Zealand, was found to be consistently associated with a newly emerging potato zebra chip (ZC) disease in Texas and other southwestern states in the USA. A species-specific primer LsoF was developed for both quantitative real-time PCR (qPCR) and conventional PCR (cPCR) to detect and quantify Lso in infected samples. In multiplex qPCR, a plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
123
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 20 publications
1
123
0
1
Order By: Relevance
“…Ten specimens of T. anthrisci were tested using the real-time PCR assay of Li et al (2009). Five of six specimens from the UK and two of four samples from Sweden tested positive (Table 1).…”
mentioning
confidence: 99%
“…Ten specimens of T. anthrisci were tested using the real-time PCR assay of Li et al (2009). Five of six specimens from the UK and two of four samples from Sweden tested positive (Table 1).…”
mentioning
confidence: 99%
“…Therefore, rapidly identification and removal of CLas-positive trees are useful for reduce the spread of HLB in citrus orchards and economic losses. However, traditional field assessment based on characteristics symptom is difficult since they resemble other diseases (such as stubborn disease and tristeza) and nutritional deficiencies [3][4][5]. At present, laboratory techniques, such as polymerase chain reaction (PCR) provide accurate detection of HLB [6], but PCR is an expensive and time-consuming process.…”
Section: Introductionmentioning
confidence: 99%
“…In another spectroscopy study, it was shown that the reflection of dried ground leaves in the mid-infrared band can be used to determine the HLB status of a sample with >95% accuracy [5]. Perez has demonstrated that Raman spectroscopy can be discriminated between orange plants HLB-positive and healthy plants with PCA-LDA analysis.…”
Section: Introductionmentioning
confidence: 99%
“…and quantitative real-time PCR (Crosslin et al, 2011;Crosslin & Munyaneza 2009;Hansen et al, 2008;Li et al, 2009;Liefting et al, 2008Liefting et al, & 2009aLin et al, 2009;Lin et al, 2011a;Munyaneza et al, 2009b;Pitman et al, 2011;Ravindran et al, 2011a & b;Wen et al, & 2011. In addition, the detection of the bacterium in psyllids using PCR is relatively straightforward (Crosslin et al, 2011;Munyaneza et al, 2009b).…”
Section: Trioza Apicalismentioning
confidence: 99%
“…The uneven distribution and variation in the 'Ca. L. solanacearum' titer in different parts of infected potato plants has been observed, making the detection of this bacterium inconsistent using conventional PCR (Buchman et al, 2011b;Crosslin & Munyaneza, 2009;Li et al, 2009;Levy et al, 2011). 'Ca.…”
Section: Trioza Apicalismentioning
confidence: 99%